Removal of Cr(III) from aqueous solutions using zeolite NaY prepared from rice husk ash - Nik Malek, Nik Ahmad Nizam; Mohd. Yusof, Alias (The Malaysian Analytical Sciences Society (ANALIS), 2007)

(untitled)
The efficiency of the synthesized zeolite NaY from rice husk ash (RHA) in the removal of Cr(III) from aqueous solution was studied. Zeolite NaY was synthesized from RHA via seeding technique and the identification of its structure was by X-ray diffraction (XRD) technique and the elemental analysis was carried out by X-ray fluorescence (XRF). physicochemical properties which were related to the use of the zeolite NaY as a sorbent was also investigated. synthesized zeolite NaY has higher cation exchange capacity (CEC) than the commercial zeolite NaY due to the higher amount of sodium content in the synthesized as well as the lower ratio of silica to alumina. The synthesized zeolite together with the commercial one as comparison was used in the sorption of the Cr(III) in aqueous solution by batch sorption experiments. The kinetic study showed that the Cr(III) uptake by both zeolites were based on the pseudo second order model. Synthesized zeolite NaY exhibited greater sorption capacities than the commercial zeolite NaY since former has higher surface area and cation exchange capacity (CEC) and lower ratio of silica to alumina which have tendency to provide more exchange sites.